Deterministic patterns in single-cell transcriptomic data - Zhixing Cao; Yiling Wang; Ramon Grima (npj Systems Biology and Applications)
Abstract We report the existence of deterministic patterns in statistical plots of single-cell transcriptomic data. We develop a theory showing that the patterns are neither artifacts introduced by the measurement process nor due to underlying biological mechanisms. Rather they naturally emerge from finite sample size effects. The theory precisely predicts the patterns in data from multiplexed error-robust fluorescence in situ hybridization and five different types of single-cell sequencing platforms.